Somatization Symptoms Regulate Emotional Memory Bias in Adolescents With Major Depressive Disorder - Daming, Mo; Xin, Li; Shuwen, Hu; Pengfei, Guo; Shuai, Liu; Feng, Geng; Xiaomei, Cao; Binbin, Chen; Hui, Zhong (Frontiers in Psychiatry, 2021)
Objective: Somatization symptoms are commonly comorbid with depression. Furthermore, people with depression and somatization have a negative memory bias. We investigated the differences in emotional memory among adolescent patients with depressive disorders, with and without functional somatization symptoms (FSS). Methods: We recruited 30 adolescents with depression and FSS, 38 adolescents with depression but without FSS, and 38 healthy participants. Emotional memory tasks were conducted to evaluate the emotional memory of the participants in the three groups. The clinical symptoms were evaluated using the Hamilton Depression Rating Scale (HDRS) and the Children’s Somatization Inventory (CSI). Results: The valence ratings and recognition accuracy rates for positive and neutral images of adolescent patients were significantly lower than those of the control group (F = 12.208, P < 0.001; F = 6.801, P < 0.05; F = 14.536, P < 0.001; F = 6.306, P < 0.05; respectively); however, the recognition accuracy rate for negative images of adolescent patients of depression without FSS was significantly lower than that of patients with FSS and control group participants (F = 10.316, P < 0.001). These differences persisted after controlling for HDRS scores. The within-group analysis revealed that patients of depression with FSS showed significantly higher recognition accuracy rates for negative images than the other types (F = 5.446, P < 0.05). The recognition accuracy rate for negative images was positively correlated with CSI scores (r = 0.352, P < 0.05). Conclusion: Therefore, emotional memory impairment exists in adolescent patients of depression and FSS are associated with negative emotional memory retention.